Consumer Trust In A Web-Based Tracking System At A Jakarta Logistics Company - Saribanon, Euis; Pribadi, Sulistya; Ningsih, Septiana Adi; Mawarni, Anissa Putri Indah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2024)
This study aims to analyze the relationship between service quality, consumer experience and consumer satisfaction through consumer trust. The population in this study is JNE consumer and the sample size collected was 150 respondents. The sample selection was carried out nonprobability through a questionnaire. Data analysis using the Partial Least Squares (PLS) method. The results of this study indicate that (1) consumer trust has a significant and positive influence on consumer satisfaction. (2) Service quality has a significant and positive influence on consumer trust. (3) service quality has a significant and positive influence on consumer satisfaction. (4) consumer experience has a significant and positive influence on consumer trust. (5) consumer experience has a significant and positive influence on consumer trust. (6) consumer experience has a significant and positive influence on consumer satisfaction. (7) service quality has a significant and positive influence on consumer satisfaction.